Pengaruh Mobilisasi Dini terhadap Penurunan Skala Nyeri dan Peningkatan Rentang Gerak pada Pasien Pasca Sectio Caesarea di RSD Gunung Jati Kota Cirebon - Sofiyati Sofiyati; Ruswati Ruswati; Neny Listiyowati; Nanda Saqinah Aprilia (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Background: Severe preeclampsia is characterized by increased blood pressure, oedema, and even proteinuria. According to WHO (2020) the prevalence of SC method indicating preeclampsia is 7%, Indonesia is 13.4%, West Java is around 12%, Cirebon City is around 23.7%. Objective: To gain real experience in providing maternity nursing care to Mrs. I with acute pain nursing problems due to postoperative Sectio Caesarea for indications of PEB in the Endang Geulis room, Gunung Jati Hospital, Cirebon City. Methods: Descriptive design in the form of a case study (case study). Population: A total of 1 respondent post SC patient indicating PEB with 1 sample selected according to the inclusion and exclusion criteria. Nursing care for post sectio caesarea patients with indications of severe preeclampsia (PEB) focused on acute pain nursing problems. The study used postpartum assessment sheet including subjective and objective data, Numeric Rating Scale, tensimeter, stethoscope. Results: The patient complained of pain in the postoperative SC wound in the lower abdomen with a length of 10 cm horizontally. The main diagnosis is acute pain with a pain scale of 6. The nursing plan is to do early mobilization. Nursing implementation carried out is to perform early mobilization techniques. Evaluation found that the problem was resolved on the third day where the pain scale decreased from 6 to 2. Conclusion: This study found that the action of early mobilization techniques that had been carried out was successful. Suggestion: This research is expected to be useful for nursing services or education in providing nursing care.